2017
DOI: 10.2176/nmc.ra.2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Review of Current Evidence Regarding Surgery in Elderly Patients with Meningioma

Abstract: The Japanese population features the highest rate of elderly individuals worldwide. Moreover, Japan has the highest number of computed tomography/magnetic resonance imaging devices in the world, which has led to an increase in the incidental detection of meningioma in healthy elderly patients. Many previous papers have discussed the risks and indications for surgery in this patient population, but available information remains insufficient, and the definition of “elderly” has not been standardized. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 83 publications
2
14
2
Order By: Relevance
“… 21) Another study showed that both 1-year and 5-year mortality rates were comparable with those for unselected cohorts and emphasized the importance of assessment of preoperative performance status and comorbidities, especially for elderly patients. 22) Combined with our results, we believe that mortality in elderly patients would be similar to that in younger patients or in at least age-matched controls if the indications for surgery are adequately considered.…”
Section: Discussionsupporting
confidence: 77%
“… 21) Another study showed that both 1-year and 5-year mortality rates were comparable with those for unselected cohorts and emphasized the importance of assessment of preoperative performance status and comorbidities, especially for elderly patients. 22) Combined with our results, we believe that mortality in elderly patients would be similar to that in younger patients or in at least age-matched controls if the indications for surgery are adequately considered.…”
Section: Discussionsupporting
confidence: 77%
“…These rates were similar to those observed in previous studies; the rates of mortality and complications after surgery were reported as 0.5-1.5%, and 6.8-14.8% respectively [5,8,15,27]. A recent systematic review reported that in elderly patients with meningiomas, the rate of one-year postoperative mortality and neurological complications after surgery ranged from 2.7-49.4% and from 0-16.7%, respectively [9]. mFI scores and age as predictors of surgical complications and worsening…”
Section: Discussionsupporting
confidence: 89%
“…However, we found no signi cant association between advanced age and in-hospital mortality. According to a recent systematic review of elderly patients with meningioma surgery, the rate of in-hospital mortality, worsening of the postoperative performance status, neurological de cits, and general complications ranged widely based on the reports and were not necessarily associated with advanced-age [9].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 18 , 19 ] Similarly, age has been correlated with poorer outcomes in meningiomas in the absence of careful consideration of preoperative medical risk factors that may disproportionally affect older patient populations. [ 6 , 9 , 11 , 13 , 21 , 23 , 29 ] Several case series have reported age as an important prognostic factor for infratentorial tumor outcomes. [ 1 , 3 , 23 ] This literature highlights the importance of considering medical comorbidities, age, tumor location, and surgical approach when treating older infratentorial tumor patients.…”
Section: Introductionmentioning
confidence: 99%